IMPACT OF COMPETENCY-BASED EDUCATION ON STUDENT ACADEMIC PERFORMANCE AND SELF-DIRECTED LEARNING BEHAVIORS IN HIGHER EDUCATION - A. , Deepan; Djabbarova , Yulduz (Scientific practical conference, 2025)
Competency-Based Education (CBE) has emerged as a transformative pedagogical approach that prioritizes mastery of skills and learning outcomes over traditional time-bound instructional models. This study investigates the impact of CBE on student academic performance and self-directed learning behaviors in higher education. Using a descriptive-methods research design, the study examines how competency-focused curricula, assessment, and instructional strategies influence students’ achievement levels and their capacity to take ownership of their learning. Findings reveal that CBE contributes to improved academic performance by enabling learners to progress at their own pace, demonstrate mastery through iterative assessments, and engage in personalized learning pathways. Moreover, CBE significantly strengthens self-directed learning behaviors by fostering autonomy, intrinsic motivation, goal setting, and reflective practices. The results highlight the potential of CBE to enhance both academic outcomes and lifelong learning competencies, making it a promising model for modern higher education systems seeking innovation, flexibility, and learner-centered practices.